Characterization of Multiphase Mixtures of Calcium Aluminates and Magnesium Aluminate Spinel Using Time‐Gated Raman Spectroscopy. Issue 8 (29th April 2020) - Gyakwaa, Francis; Aula, Matti; Vuolio, Tero; Alatarvas, Tuomas; Shu, Qifeng; Huttula, Marko; Fabritius, Timo
Abstract : In aluminum‐killed calcium‐treated steels, the characterization of multiphase oxides found in the CaO–MgO–Al2 O3 system is essential for the study of inclusion formation, modification, and the control process. Herein, Raman spectroscopy is used as a characterization technique for the multiphase mixtures of MgO·Al2 O3 spinel and calcium aluminate phases of C12A7, C3A, and CA. Multiphase samples of C12A7–CA–MA and C12A7–C3A–MA are synthesized from MgO·Al2 O3 spinel and calcium aluminates with varying phase content. The relative intensity of the Raman peaks is qualitatively used for the most primary phases present in the sample. Regression models are also identified for predicting the phase composition. Prediction model identification is conducted using the successive projection algorithm (SPA) for feature selection and the partial least squares regression (PLS) model as a regressor. The identified prediction models show a reasonably good prediction performance. Herein, the time‐gated Raman spectroscopy technique to characterize the multiphase mixture of magnesium aluminate spinel and calcium aluminate phases of CA, C12A7, C3A is used, and the potential application for inclusion characterization is demonstrated. Abstract : The use of Raman spectroscopy for the identification and characterization of the ternary mixture of magnesium aluminate spinel and calcium aluminate phases and the potential application for inclusion characterization are demonstrated. Prediction model identification such as the partial least squares regression (PLS) model for predicting the phase composition present in the samples is described.